Dynamic comparison of early immune reactions and immune cell reconstitution after umbilical cord blood transplantation and peripheral blood stem cell transplantation - Zhao, Xuxu; Wang, Wenya; Nie, Shiqin; Geng, Liangquan; Song, Kaidi; Zhang, Xinyi; Yao, Wen; Qiang, Ping; Sun, Guangyu; Wang, Dongyao; Liu, Huilan (Frontiers in Immunology, 2023)
Umbilical cord blood transplantation (UCBT) and peripheral blood stem cell transplantation (PBSCT) are effective allogeneic treatments for patients with malignant and non-malignant refractory hematological diseases. However, the differences in the immune cell reconstitution and the immune reactions during initial stages post-transplantation are not well established between UCBT and PBSCT. Therefore, in this study, we analyzed the differences in the immune reactions during the early stages (days 7-100 post-transplantation) such as pre-engraftment syndrome (PES), engraftment syndrome (ES), and acute graft-versus-host disease (aGVHD) and the immune cell reconstitution between the UCBT and the PBSCT group of patients. We enrolled a cohort of patients that underwent UCBT or PBSCT and healthy controls (n=25 each) and evaluated their peripheral blood mononuclear cell (PBMC) samples and plasma cytokine (IL-10 and GM-CSF) levels using flow cytometry and ELISA, respectively. Our results showed that the incidences of early immune reactions such as PES, ES, and aGVHD were significantly higher in the UCBT group compared to the PBSCT group. Furthermore, in comparison with the PBSCT group, the UCBT group showed higher proportion and numbers of naïve CD4+ T cells, lower proportion and numbers of Tregs, higher proportion of CD8+ T cells with increased activity, and higher proportion of mature CD56dim CD16+ NK cells during the early stages post-transplantation. Moreover, the plasma levels of GM-CSF were significantly higher in the UCBT group compared to the PBSCT group in the third week after transplantation. Overall, our findings demonstrated significant differences in the post-transplantation immune cell reconstitution between the UCBT and the PBSCT group of patients. These characteristics were associated with significant differences between the UCBT and the PBSCT groups regarding the incidences of immune reactions during the early stages post transplantation.